General Electric Unattended Power System Study. Addendum - Bregenzer, D D (1980)
The General Electric 2 KW(e) Unattended Power System Study was conducted in 1976-77 to analyze the cost and risk associated with the development of alternative power systems capable of supplying 2 KW(e) in an unattended mode in an Arctic environment. The study concluded that a diesel power system was the most attractive alternative for an unattended radar (UAR) station prime power generation and distribution system. This paper extends the General Electric Study by examining three of the candidate systems in more detail and updating cost estimates based on a change in the power requirements to 5KW(e). The three systems chosen for further examination are diesel power systems, fuel cell power plants, and an organic Rankine cycle turbogenerator, the Ormat Energy Converter.